SKBI Big 5 Survey 2020 August - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
The COVID-19 pandemic led to whopping downward revisions to 2020 real GDP growth among the Big5 economies, on average greater than 7%-points (ranging from roughly 3.5%-points for China to more than 10%-points for India). The forecast revisions to headline inflation were less sizable and more uneven, perhaps because of the confluence of supply and demand influences. The 2021 median GDP forecast is expected to turn positive overall, with a balanced risk assessment for most of the Big5 (but a coin toss in IN and US), but the growth reversal is likely to be highly uneven. While China regains its prior peak GDP level faster than the other countries, none of the Big5 are projected to revert to their previous average growth momentum by next year. Although most see the current monetary policy response as sufficient (unclear in IN), the views on the fiscal response are more equivocal (insufficient in IN). Hence, relative to the prevailing policy stance, central banks are generally expected to be on-hold in 2020 and 2021. Conversely, the majority still anticipate fiscal policy to step-up this year, perhaps holding steady in 2021. The survey results suggest that COVID-19 is likely to reduce trend growth for three of the five biggest economies (too early to assess for CN and less clear for US). But participants appear more divided on the potential impact on future growth prospects from a higher fiscal debt ratio (potentially negative for IN, though not for CN, and too early to assess for others).